Material-Tailored tool inserts for injection moulding using material extrusion multi-material Additive Manufacturing - Vetter, Johannes; Beneder, Samuel; Schmidt, Michael (13th CIRP Conference on Photonic Technologies, LANE 2024, 2024)
Tool inserts for injection moulding must serve various requirements being contradictive to each other. The best approach to enhance the functionality of a tool insert, i.e., providing good wear and corrosion resistance as well as good toughness, is to employ a multimaterial approach. This study investigates a concept for manufacture of a material-Tailored multi-material tool insert using Material Extrusion additive manufacturing of metals (MEX/M). The processing of AISI A2 (1.2363) and AISI 420 (1.2083) steel as a wearresistant and corrosion-resistant material, respectively, in combination with AISI H11 (1.2343) as a tough bulk material were investigated. The eligibility of these materials for co-sintering was evaluated based on shrinkage and resulting density after sintering. A material-Tailored tool insert was manufactured by means of MEX/M demonstrating its capability for multi-material additive manufacturing. Elemental distribution at the interface was analysed. Surface quality of the multi-material tool insert was evaluated taking into account extruder trajectories.
CRIS-Team Scopus Importer:2024-09-27
Keywords: Co-sintering; interface analysis; Material extrusion; Multi-material additive manufacturing